1987
DOI: 10.1007/bf01422664
|View full text |Cite
|
Sign up to set email alerts
|

Fading phenomena of azo oil dye in anionic-nonionic surfactant solutions II. Effects of alkyl and/or oxyethylene groups in nonionic surfactant on the fading rate

Abstract: Abstract:The effects of alkyl and/or oxyethylene groups in a nonionic surfactant on the fading phenomena of 4-phenylazo-l-naphthol (4-OH), which occur in aqueous solutions of anionic-nonionic surfactant systems, are described; these systems are sodium dodecyl sulfate (SDS) -alkyl poly(oxyethylene) ethers (CmPOEn, m = 12,14,16, and 18 at n = 20; n = 10, 20, 30, and 40 at m = 16). The fading phenomenon is observed when 4-OH is added to the anionic-nonionic mixed surfactant solutions at a molar ratio of i : 1. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…In previous papers [6][7][8] we have reported that the fading phenomena observed in anionic-nonionic mixed surfactant solutions are caused by the singlet The singlet oxygen lifetime, however, is too short for the color of the dye to fade in surfactant-free solutions. According to Merkel and Kearns' study [14], the difference in singlet oxygen lifetime is due to kinds of solvents, which they describe in terms of intermolecular electrical-to-vibration energy transfers.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In previous papers [6][7][8] we have reported that the fading phenomena observed in anionic-nonionic mixed surfactant solutions are caused by the singlet The singlet oxygen lifetime, however, is too short for the color of the dye to fade in surfactant-free solutions. According to Merkel and Kearns' study [14], the difference in singlet oxygen lifetime is due to kinds of solvents, which they describe in terms of intermolecular electrical-to-vibration energy transfers.…”
Section: Discussionmentioning
confidence: 98%
“…The polar nature of this acid is fairly strong and it dissociates slightly. In previous papers [6][7][8], we have reported that the fading rate of 4-OH is small in the mixed system in which two kinds of rich micelles coexist. Therefore, it is thought that anionic-rich micelles, formed easily with an increasing amount of octanoic acid solubilized, and that the fading rate of 4-OH consequently decreased with increasing its concentration.…”
Section: Effect Of Micellar Size On the Fading Phenomena Of 4-ohmentioning
confidence: 99%
See 1 more Smart Citation